THE POTENTIAL FOR HALAL TOURISM DEVELOPMENT IN THE NATUNA GEOPARK AREA FROM A MAQASID AL-SHARIAH PERSPECTIVE - Sayed Muktarhadi; Nikmatul Rahmah Isnaniah; Kartubi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the halal tourism potential and maqasid al-shariah-based development strategy of the Natuna Geopark, a National Geopark encompassing 27,233.85 square kilometers of land and sea in Ranai, Natuna Regency, Indonesia's northernmost maritime border territory. The study aims to analyze the natural resource, cultural heritage, and infrastructure potential of the geopark as a halal tourism destination, and to construct a maqasid al-shariah-based strategy for its sustainable and Muslim-friendly development. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, participant observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the geopark possesses an exceptional convergence of 200-million-year-old geological formations, Srivijaya civilizational heritage, and living Malay Islamic cultural identity, yet remains structurally underdeveloped as a halal destination due to the absence of halal certification, Muslim-friendly geosite infrastructure, and any deliberate Islamic development framework. In response, this study constructs a five-pillar maqasid al-shariah-based development strategy encompassing hifz al-din, hifz al-nafs, hifz al-aql, hifz al-nasl, and hifz al-mal, offering a transferable model aligned with SDG 8, SDG 10, SDG 11, and SDG 16 for sustainable halal geoheritage tourism development in Muslim-majority border communities.